Reflections on the electronic SUS in the dental work process in primary care - Teixeira, Joás de Araújo; Marcelino, William Max do Nascimento; Ribeiro, Adriana da Costa (Seven Editora, 2024)
The electronic SUS, or E-SUS, is a strategy whose main guideline is to allow the follow-up of each patient by automating the work process and the production of information for professionals in primary care. This strategy is characterized by an electronic SUS to facilitate and collaborate with the organization of the work of health professionals, which directly influences the quality of the service provided. The implementation of the E-SUS has been developed gradually because, being a new tool, it encounters difficulties such as the extension of the country’s territory and the availability of the service structure. The positive contribution of E-SUS to the work process of the dental surgeon in relation to the optimization and integration of information is obvious, but several aspects must be considered for its use to be effective for the work process. DOI:https://doi.org/10.56238/sevened2024.007-047